BIOREMEDIATION COLUMN STUDY OF PETROLEUM HYDROCARBON-CONTAMINATED SOIL - Amelia Situmorang, Rizka
Fuel oil contamination, often caused by tank leaks, can be addressed using in-situ bioremediation methods such as bioventing, nutrient addition, and the introduction of external bacteria. These methods can reduce excavation and transportation costs. This study aims to enhance the efficiency of contaminant reduction in soil to meet quality standards. The experiment used columns with different treatments: Control as a blanko, Natural Attenuation as a biological process control, Natural Attenuation Aeration, BA with bioaugmentation and aeration, BS with biostimulation and aeration, and Bioaugmentation-Biostimulation as a combination of BA and BS treatments. After 33 days, the Biostimulation column achieved the highest TPH reduction of 99%, decreasing from 9583 mg/kg to 72.63 mg/kg. The Bioaugmentation-Biostimulation column removed 98% of TPH, followed by Bioaugmentation (97%), NA AE (93%), and NA (89%), while the control column removed 66%. Nutrient addition proved more efficient due to the soil's low permeability, which hampers bacterial distribution. Indigenous bacteria's effectiveness allowed for competition with external bacteria, and fertile soil supported natural bacterial growth. By the end of the study, microbial concentration increased from 104 cfu/gram to 107 cfu/gram. Statistical analysis showed significant differences only in the control column, with no significant differences in bioremediation columns. However, kinetic analysis revealed that biostimulation had a half-life three times faster than NA, with the smallest half time for biostimulation (6.81 days) compared to NA (20.45 days). At the end of the process, 6-7 compounds remained from the initial 63, with added acetic acid lowering soil pH, while the control column's pH remained stable at 7.